Feasibility and safety of intrapulmonary percussive ventilation in spontaneously breathing, non-ventilated patients in critical care: A retrospective pilot study. (May 2021) - Hassan, Anwar; Milross, Maree; Lai, William; Shetty, Deepa; Alison, Jennifer; Huang, Stephen
Background: Intrapulmonary percussive ventilation is used in various clinical settings to promote secretion clearance, reverse or treat atelectasis and improve gas exchange. Despite a few studies reporting the use of intrapulmonary percussive ventilation in critical care, the available data remain insufficient, contributing to weaker evidence toward its effectiveness. Also, there is a paucity of studies evaluating the safety and feasibility of intrapulmonary percussive ventilation application in critical care. This retrospective pilot study has evaluated the safety and feasibility of intrapulmonary percussive ventilation intervention in non-intubated patients admitted to an intensive care unit. Methods: The medical records of 35 subjects were reviewed, including 22 subjects who received intrapulmonary percussive ventilation intervention and 13 subjects matched for age, sex, and primary diagnosis who received chest physiotherapy. The records were audited for feasibility, safety, changes in oxygen saturation, chest X-ray changes, and intensive care unit length of stay. Results: A total of 104 treatment sessions (IPV 65 and CPT 39) were delivered to subjects admitted with a range of respiratory conditions in critical care. Subjects completed 97% of IPV sessions. No major adverse events were reported with intrapulmonary percussive ventilation intervention. Intensive care unit length of stay in the intrapulmonary percussive ventilation group was 9.6 ± 6 days, and in the CPT group, it was 11 ± 9 days ( p = 0.59). Peripheral oxygen saturation pre to post intervention was 92% ± 4 to 96% ± 4 in IPV group and 95% ± 4 to 95% ± 3 in the CPT group. Conclusion: Application of intrapulmonary percussive ventilation intervention was feasible and safe in non-ventilated adult patients in critical care.